Survival of children with endemic Burkitt lymphoma in a prospective clinical care project in Uganda. Issue 9 (3rd June 2019) - McGoldrick, Suzanne M.; Mutyaba, Innocent; Adams, Scott V.; Larsen, Anna; Krantz, Elizabeth M.; Namirembe, Constance; Mooka, Peter; Nabakooza, Susan; Ndagire, Mariam; Mubiru, Kelvin; Nabwana, Martin; Nankinga, Rose; et al.
Abstract: Purpose: "Endemic" Burkitt lymphoma (BL) is a common childhood cancer in Africa. Social and treatment factors may contribute to poor survival. With the aim of improving BL outcomes in Uganda, we undertook a comprehensive project (BL Project) that provided diagnostic support, access to standard chemotherapy, nutritional evaluations, and case management. We evaluated survival of children with BL in the context of the project. Patients and methods: Patients followed by the BL Project who consented to research were enrolled in this study. Children with a pathology diagnosis consistent with BL were eligible. Data were collected prospectively. First‐line chemotherapy generally consisted of six cycles of cyclophosphamide, vincristine, low‐dose methotrexate (COM). We used Kaplan–Meier and Cox regression analyses to evaluate factors associated with overall survival (OS). Results: Between July 2012 and June 2017, 341 patients with suspected BL presented to the BL Project. One hundred eighty patients with a pathology‐based diagnosis were included in this study. The median age was seven years (interquartile range, 5–9), 74% lived ≥100 km from the Uganda Cancer Institute, 61% had late‐stage disease, 84% had ECOG performance status < 3, 63% reported B‐symptoms, and 22% showed neurologic symptoms. Fewer than 10% abandoned therapy. The four‐year OS rate was 44% (95% CI, 36%–53%). In a multivariate model, ECOG status was significantly associated with mortality. Conclusion: The BL Project reduced effects of lacking supportive care and oncology resources, and allowed patients from Uganda to receive curative intent therapy with minimal loss to follow‐up. Nonetheless, OS remains unacceptably low. Improved therapeutic approaches to endemic BL are urgently needed in Africa.